Character Education Values in This Children's Short Story Collection Wants to Pee in Jakarta: Its Use in High School Learning - Azizah, Hilma Azmi; Purnani, Siwi Tri; Hasanah, Dina Fitria (Journal of English Language and Education, 2025)
The purpose of this study is to describe the values of character education in the short story collection "This Child Wants to Pee in Jakarta". The values of character education in the short story collection "This Child Wants to Pee in Jakarta" are religious character values, patience, attention, liking to listen to advice, trying hard, fighting for the truth, justice, honesty, positive thinking/husnudzan, persistence, independence, never giving up, liking to read, and ideals. Religious character values related to divinity can be applied indirectly through worship activities at school. Likewise, other character values can be closely related to the teaching of character education at school. And its utilization in learning activities in high school. This research is a qualitative descriptive research. The data of this research are in the form of sentences/paragraphs in event units in five short stories "This Child Wants to Pee in Jakarta" by Ahmad Tohari, "Hakim Sarmin" by Agus Noor, "Basa-Basi" by Jujur Prananto, "Two Singers" by Budi Darma, and "A Bottle of Rain of Sapardi" by Joko Pinurbo. The instrument in this research is the researcher himself who is equipped with a set of theories and concepts regarding the values of character education. The data analysis method used in this research is content analysis, while the data analysis technique in this research is descriptive qualitative.